Cellular tropism and genetic stability of African pygmy hedgehog adenovirus 1 during serial passage - Wen, Rongduo; Takemae, Hitoshi; Oba, Mami; Mizutani, Tetsuya; Omatsu, Tsutomu; Ochiai, Hideharu (Japanese Journal of Veterinary Research, 2025)
African pygmy hedgehog adenovirus 1 (AhAdV-1) was isolated from a hedgehog exhibiting respiratory symptoms in Japan. In this study, we evaluated the cellular tropism of AhAdV-1 using various mammalian cell lines and investigated its genetic stability during long-term serial passage in MDCK cells. AhAdV-1 exhibited high replication efficiency in MDCK, MDBK, CPK, and Vero cells but showed limited growth in BHK, HeLa, and HC11 cells. No replication was detected in RAW 264.7 and 3LL cells. Since MDCK cells demonstrated the highest viral production, serial passage was performed up to 110 passages. Whole-genome analysis revealed only four mutations, suggesting that AhAdV-1 is a genetically stable virus. These findings contribute to the understanding of the host range and evolutionary stability of AhAdV-1.